Representasi Ideologi dalam Pemberitaan Konflik India-Pakistan di aljazeera.net Perspektif Analisis Wacana Kritis Norman Fairclough - Erliana, Leni; Warni, Ade; Al Masyhuri, Amin; Almardhiyah, Alaina; Ibadillah, Banna Irfan (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This research aims to reveal the ideological representation in aljazeera.net news coverage of the India–Pakistan conflict. The method used is a descriptive qualitative approach, drawing on Norman Fairclough’s Critical Discourse Analysis. The research focuses on the representation of grammatical elements in clauses, such as types of processes (action, event, state, and mental) and types of participants (actor, victim, and nominal). The data were collected from 14 online news articles on aljazeera.net published between April to May 2025. The data were analyzed by examining linguistic elements at the clause level in the selected news texts, focusing on process types and participant roles based on Norman Fairclough’s textual analysis framework. Each clause was classified into process types (action, event, state, and mental), and the participants involved were asked to identify patterns of agency and ideological representation. In addition, the analysis considered the use of passive constructions, nominalization, and the omission of social actors as linguistic strategies that shape ideological meanings in news discourse. The findings show that the media consistently portrays military actions by India and Pakistan as reactive measures rather than unilateral aggression. Aljazeera.net also applies representational strategies to frame the conflict symmetrically, making both parties appear morally justified. The use of passive constructions, nominalization, and the omission of social actors in several news excerpts demonstrates the media’s effort to shape public opinion in a neutral yet ideological manner. Thus, aljazeera.net not only delivers information but also constructs social reality through strategically selected language.